The dangerous and contradictory prognostic significance of PVR<3WU when TAPSE<16mm in postcapillary pulmonary hypertension. (23rd July 2020) - Raitière, Olivier; Berthelot, Emmanuelle; Fauvel, Charles; Guignant, Pierre; Si Belkacem, Nassima; Sitbon, Olivier; Bauer, Fabrice
Abstract: Aims: In 2019, pulmonary vascular resistance (PVR) < 3WU was adopted to stratify patients at low risk in pulmonary hypertension due to left heart disease (PH‐LHD) as well those with isolated PH‐LHD. We sought to evaluate whether supervised machine learning with decision tree analysis, which provides more information than Cox Proportional analysis by forming a hierarchy of multiple covariates, confirms this risk stratification. Methods and results: Two hundred two consecutive patients (mean age: 69 ± 11 years, female: 42%) with mean pulmonary artery pressure ≥ 20 mmHg and wedge pressure > 15 mmHg were recruited. Transpulmonary pressure gradient ⩾̸ 12 mmHg, PVR ⩾̸ 3WU, diastolic pressure gradient ⩾̸ 7 mmHg, pulmonary arterial capacitance < 1.1 mL/mmHg, tricuspid annular plane systolic excursion (TAPSE) < 16 mm, peak systolic tissue Doppler velocity < 10 cm/s, right ventricular end‐diastolic area ⩾̸ 25 cm 2 were the seven categorical values entered into the model due to their prognostic significance in PH. We used the chi‐squared automatic interaction detection method to predict mortality. Each node and branch were compared using survival analysis at 6‐year follow‐up. Mean pulmonary artery pressure, wedge pressure, cardiac index, and PVR were 40.3 ± 10.0 mmHg, 22.3 ± 7.1 mmHg, 2.9 ± 0.8 L/min/m 2, and 3.6 ± 2.1WU, respectively. Among the seven dichotomous, TAPSE was first selected following by PVR. Compared with patients with PVR < 3WU and TAPSE ⩾̸ 16 mm, patients with PVR ⩾̸ 3WU and TAPSE ⩾̸ 16 mm, or patients with PVR ⩾̸ 3WU and TAPSE<16 mm had significantly increased mortality, HR = 3.0, 95% CI = [1.4–6.4], P  = 0.006 and HR = 3.3, 95% CI = [1.6–6.9], P  = 0.002, respectively, while patients with PVR < 3WU and TAPSE < 16 mm exhibited the worst prognosis, HR = 7.2, 95% CI = [3.3–15.9], P  = 0.0001. Conclusions: Used for solving regression and classification problems, decision tree analysis confirms that PVR and TAPSE have to be analysed together in PH‐LHD and revealed the dangerous and contradictory prognostic significance of PVR < 3WU when TAPSE<16 mm.